Jonah in the shadows of Eden - Berger, Yitzhak (Indiana Studies in Biblical Literature, 2016)
Cover -- Contents -- Acknowledgments -- Abbreviations -- A Note to the Reader -- 1. Escape to Eden -- 2. Wrathful Moralist -- 3. Peaceful Dove -- 4. A Song of Thanks in Waters of Eden -- 5. Nautical and Hermeneutical Dilemmas -- Notes -- Bibliography -- Index of Names and Subjects -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- Y -- Z -- Index of Biblical Citations